The Influence of Learning Communities and Participatory Leadership on the Leadership of Driving Teachers - Dewi Ratnawati; Widya Kusumaningsih; Nurkolis Nurkolis; Pinurba Anindita (Yayasan Keluarga Guru Mandiri, 2025)
The leadership of driving teachers is crucial in the learning process, especially when facing technological advancements supporting educational processes. This study aims to analyze the influence of learning communities and participatory leadership on the leadership of driving teachers. The approach used is quantitative with a correlational research design. The research population consists of 70 teachers, who are also used as the sample. Data was collected through questionnaires and analyzed using descriptive analysis techniques and prerequisite tests (normality test, multicollinearity, heteroscedasticity, and linearity). Hypothesis testing was carried out through simple and multiple linear regression. The study results show that the learning community has a correlation of 0.738 and significantly influences the leadership of driving teachers by 74.5%. Participatory leadership correlates 0.781 and significantly influences the leadership by 70.9%. Simultaneously, the learning community and participatory leadership significantly influence the leadership of driving teachers with a coefficient of determination of 73.5%. The regression equation is ? = 12.383 + 1.020 X1 + 1.881 X2. This study provides insights for schools and policymakers to develop collaborative learning strategies and more inclusive leadership.